Challenges of Leadership from Narratives of Female Principals of Rural Secondary Schools in Vhembe District of South Africa - Livhalani Bridget Sinyosi; Onoriode Collins Potokri (Researchers World - International Refereed Social Sciences Journal, 2021)
Purpose: This study investigated the challenges school leaders in South African rural secondary schools face. The leaders in this study are female principals. Methodology: Qualitative research method was utilized. Purposive sampling procedure was used to identify and select participants. Ten (10) female principals from ten (10) secondary schools in circuits within the Vhembe district of Limpopo Province in South Africa served as the participants. Focus group discussion was used as the data collection tool. The data were analysed using thematic analysis. Findings: The study findings revealed that the major challenges facing the female principals emanate from learners’ ill-discipline and unwillingness to learn, drug, alcohol, and substance usage and abuse, lack of respect and negative attitudes from teachers, teachers’ unwillingness to work and lack of corporation, lack of acceptance within the school context and the society at large, parents unavailability and unwillingness to support learners’ education, and gender discrimination and societal stereotype. The findings show that the challenges female principals face in their leadership roles has extrapolative impact on their willingness to remain or leave leadership. Implications: By implications, dealing with the challenges through contextual support mechanism to complement affirmative policies and legislations is a good step towards gender equality ideologies that liberal feminism promotes. Originality: Till now, there are few studies about female school leaders in rural provinces of South Africa. Unique to this study, is the theoretical lens used and the district where the study was conducted.